Bimbingan Pengendalian Hama dan Penyakit Terpadu pada Petani Kubis di Kampung Sota - Anwar Anwar; Mani Yusuf; Maya Sari Rupang; Wa Ode Asryanti Wida Malesi (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Sota Village is one of the villages located in Sota District, Merauke Regency with an area of 698.13 km2 of the four other villages in Sota District, Sota Village is the largest area which reaches 26.85% of the Sota District area. Most of the agricultural area in Sota District is located around residential areas is the wet and dry soil. One of the dry soil in Sota Village is dominated by horticultural plants such as Brassica oleraceae L. plants. Brassica oleraceae L. is a horticultural plants that is favored by consumers in the city of Merauke. However, the problem that greatly affects the production of Brassica oleraceae L. plants is the attack of pests and diseases. The approach method to solve these problems is by way of guidance and assistance to farmers through a persuasive approach by applying the concept of Integrated Pest and Disease Management (IPDM). This activity is expected to provide an understanding to Brassica oleraceae L. farmers regarding the proper and correct use of pesticides according to regulations so that plant pests do not become resistant, and in the end can increase the growth and production of Brassica oleraceae L. plants. The evaluation results show that farmers have carried out pest and disease control by following the applicable regulations or the standard operating procedure.